‘Tierra pa todos’ cooperative: contributions to the evaluation of an associative model of colonization - Arbeletche Favat, Pedro; Buenahora, Marcelo (Cooperativismo & Desarrollo, 2023)
The objective of this work was to make contributions for the evaluation of the public policy of access to land for associative groups, carried out from the study of the conformation and development of the cooperative organization Tierra pa todos of rural wage earners who accessed fields of the National Institute of Colonization in the east of the department of Paysandú of the República Oriental del Uruguay, during the decade of 2005-2015. It focused on the case of study, the Cooperative “Tierra Pa Todos” that accessed two fractions of the field in Colonia Dr. Miguel C. Rubino. This award is part of the non-traditional colonization model implemented by the INC as of 2005, where the award of land to groups of rural wage earners and organized family producers is prioritized. The methodology was based on qualitative research techniques involving the main social through the construction of variables and indicators that contributed to the results of the work. Individual and group semi- structured interviews, participatory diagnostic tools such as SWOT analysis and documentary review provided by the group were used. Among the conclusions, it is highlighted that the rural wage earners in this case who accessed land associatively, increased their productive capacity and livestock assets both individually and collectively and thus improved their income, thus complementing their wages and / or economy. they had before opted for this proposal. It also allowed them to improve livestock purchases and sales while accessing technical assistance.